Do Perceptions of Legitimacy and Fairness Matter in Prison? Examining How Procedural and Distributive Justice Relate to Misconduct - Campbell, Christopher M. (Criminal justice and behavior, 2020)
Recent scholarship suggests disciplinary protocols and incarcerated individuals’ perceptions of procedural justice toward correctional officers may be important in influencing one’s behavior and prison order. This study provides an examination of procedural and distributive justice in prison. We surveyed a stratified random sample of 144 respondents incarcerated in Maine state prisons about their perceptions toward the disciplinary process and corrections officers to assess the relationship between such views and patterns of institutional misconduct. Findings provide partial support for the procedural justice perspective in prison. Normative perceptions (e.g., legitimacy) are positively associated with voluntary deference measures while instrumental perceptions of officer effectiveness in controlling behavior are positively associated with respondent perceived risk. These results supply insight into theory development related to voluntary deference. Similarly, these findings can inform which relationships between officers and respondents may hold the potential to promote rule compliance and prison order.